1993
DOI: 10.1128/jvi.67.8.4484-4491.1993
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus pathogenesis in transgenic mice is altered by the homeodomain protein Hox 1.3

Abstract: The DNA sequence TAAT is the core binding motif for the mouse homeodomain protein Hox 1.3 (proposed new name, Hoxa-5). These sequences are present within the multiple TAATGARAT regulatory motifs in the promoters of the immediate-early genes which control herpes simplex virus type 1 replication. To investigate the role of this homeodomain protein in the regulation of herpes simplex virus gene expression and pathogenesis, transgenic mice containing a mouse Hox 1.3 cDNA under the control of the virusand interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Sections from the eyes that were assayed by in situ PCR were also evaluated for evidence of lesions by lightmicroscopic evaluation of hematoxylin-and eosin-stained sections. Other sections from the same eyes were deparaffinized and assayed for the presence of viral antigen by the avidin-biotin-peroxidase method (Vector) with HSV-1 antiserum (Dako) at a 1:1,000 dilution (25,26). As controls, uninfected mouse eyes were reacted with the HSV-1 antiserum and infected eyes were reacted with control rabbit serum in the same assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections from the eyes that were assayed by in situ PCR were also evaluated for evidence of lesions by lightmicroscopic evaluation of hematoxylin-and eosin-stained sections. Other sections from the same eyes were deparaffinized and assayed for the presence of viral antigen by the avidin-biotin-peroxidase method (Vector) with HSV-1 antiserum (Dako) at a 1:1,000 dilution (25,26). As controls, uninfected mouse eyes were reacted with the HSV-1 antiserum and infected eyes were reacted with control rabbit serum in the same assays.…”
Section: Methodsmentioning
confidence: 99%
“…Viral culture. Sections of eyelid skin and conjunctiva which had been dissected free from other ocular tissues were homogenized, and each homogenate was assayed for HSV-1 on Vero cells overlaid with methylcellulose in a standard plaque assay (26). Culture results were expressed as the number of eyes from which virus could be cultured from combined eyelid skin and conjunctiva.…”
Section: Methodsmentioning
confidence: 99%
“…The ICP4 promoter fragment was ligated (40) into the blunt-ended pNlacF plasmid (restriction digested at the SalI site and made blunt ended by treatment with Klenow enzyme) containing the Esch-erichia coli ␤-galactosidase coding sequence and including a simian virus 40 nuclear translocation signal (27). The XbaI-HindIII fragment from the final construct was isolated and purified, and approximately 200 copies were injected (17,29) into each (C57BL/6 ϫ C3H)F 1 ϫ (C57BL/6 ϫ C3H)F 1 one-cell embryo. Three founder animals (designated Tg0002, Tg6305, and Tg6307) were identified, and transgenic lines were established by brother-sister matings.…”
Section: Methodsmentioning
confidence: 99%
“…Two of the lines described in this report have been assigned designations according to the standardized rules for nomenclature in transgenic mice: line Tg6305, TgN(HS VieRp)1wm; line Tg6307, TgN(HSVieRp)2wm. Heterozygous transgenic mice and their nontransgenic control littermates were used in this study; these mice were identified by PCR using tail DNA (29,30,32) and primers (GCATCGAG CTGGGTAATAAGCGTTGGCAAT and GACACCAGACCAACTGGTAAT GGTAGCGAC) for the ␤-galactosidase coding sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation